Prediction of structural response of distressed bridge using finite element method - Krishna, Shreeram (2004)
Bridges must be evaluated to make sure they are capable of carrying the present load and most importantly the future load within the serviceability limit. The analysis of the loads consists of measuring the load distribution and the effect on the structural components. This can be done experimentally using the available field test instruments or also known Proof Load Test. The main objective of the field test is to measure the deflections, stresses and strains at the critical bridge components subjected to a predetermined load. However, field test can be expensive in terms of cost and time. The development of a realistic analytical model seems to be an alternative to provide a supplementary load capacity assessment with lesser cost and time. This paper will provide a comprehensive review on the Finite Element Model prediction on the structural response of a distressed bridge with comparison made to the actual response obtained from the field load test results. Comparison reveals that the predicted model behaves similarly to the actual bridge response under live loading but it was also noted some variation or difference in term of the magnitude of responses. These differences are mainly attributed to the existence of field factors which were not included in the model.